A multi-ethnic study of a PNPLA3 gene variant and its association with disease severity in non-alcoholic fatty liver disease - Zain, Shamsul Mohd; Mohamed, Rosmawati; Mahadeva, Sanjiv; Cheah, Phaik Leng; Rampal, Sanjay; Basu, Roma Choudhury; Mohamed, Zahurin (Springer, 2012)
The adiponutrin (PNPLA3) rs738409 polymorphism has been found to be associated with susceptibility to non-alcoholic fatty liver disease (NAFLD) in various cohorts. We further investigated the association of this polymorphism with non-alcoholic steatohepatitis (NASH) severity and with histological features of NAFLD. A total of 144 biopsy-proven NAFLD patients and 198 controls were genotyped for PNPLA3 gene polymorphism (rs738409 C>G). The biopsy specimens were histologically graded by a qualified pathologist. We observed an association of G allele with susceptibility to NAFLD in the pooled subjects (OR 2.34, 95 CI 1.69-3.24, p < 0.0001), and following stratification, in each of the three ethnic subgroups, namely Chinese, Indian and Malay (OR 1.94, 95 CI 1.12-3.37, p = 0.018; OR 3.51, 95 CI 1.69-7.26, p = 0.001 and OR 2.05, 95 CI 1.25-3.35, p = 0.005, respectively). The G allele is associated with susceptibility to NASH (OR 2.64, 95 CI 1.85-3.75, p < 0.0001), with NASH severity (OR 1.85, 95 CI 1.05-3.26, p = 0.035) and with presence of fibrosis (OR 1.95, 95 CI 1.17-3.26, p = 0.013) but not with simple steatosis nor with other histological parameters. Although the serum triglyceride level is significantly higher in NAFLD patients compared to controls, the G allele is associated with decreased level of triglycerides (p = 0.029) in the NAFLD patients. Overall, the rs738409 G allele is associated with severity of NASH and occurence of fibrosis in patients with NAFLD. Â© 2012 The Author(s).